1995
DOI: 10.1051/rnd:19950206
|View full text |Cite
|
Sign up to set email alerts
|

Transport of β-lactoglobulin and α-lactalbumin in enterocyte-like Caco-2 cells

Abstract: Summary ― The transport of [ 14 C]-radiolabelled p-lactoglobulin and a-iactaibumin through Caco-2 cell monolayers grown on permeable filters was studied in order to evaluate the different protein pathways through the intestinal epithelium. p-Lactoglobulin or a-lactalbumin (0.25-3 mg/ml) was introduced on the apical side of the monolayer and both the transport and the release of labelled material from the cells were measured following different incubation times. The labelled material was analysed by eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 20 publications
2
28
0
Order By: Relevance
“…As linoleate concentration was constant (50 µM linoleate), βlg concentration was three times smaller for a linoleate/βlg molar ratio of 3 compare to a molar ratio of 1. Native βlg has been shown to be transported into the cells (Caillard and Tome, 1995). This could explain why the kinetics of linoleate transport from the medium to the cells is affected by βlg concentration.…”
Section: Discussionmentioning
confidence: 98%
“…As linoleate concentration was constant (50 µM linoleate), βlg concentration was three times smaller for a linoleate/βlg molar ratio of 3 compare to a molar ratio of 1. Native βlg has been shown to be transported into the cells (Caillard and Tome, 1995). This could explain why the kinetics of linoleate transport from the medium to the cells is affected by βlg concentration.…”
Section: Discussionmentioning
confidence: 98%
“…It has also been demonstrated that b-Lg from milk is taken up by the duodenal epithelium, possibly by a paracellular route [8]. In vitro studies on confluent cultures of the enterocyte-like cell line Caco-2 have confirmed the endocytic nature of b-Lg uptake, and whilst the majority of the protein was degraded intracellularly, around a third was transported across the cells [9]. The nature of the transported proteins has not been clearly defined, but circumstantial evidence, such as serum IgE, indicates that intact and degraded proteins cross the mucosal barrier.…”
Section: Digestion Of Allergensmentioning
confidence: 95%
“…To date, no common features of protein molecules or protein molecule fragments have been identified as the major cause of allergy, although some resistance to pepsin digestion is a common property [9]. Resistance to pepsinolysis has been identified using conditions that are far from physiological, as part of the allergenicity risk assessment process for target transgenes.…”
Section: Digestion Of Allergensmentioning
confidence: 99%
“…β-lactoglobulin epithelial transport has been studied using the Ussing chamber [4,23] and the Caco-2 cell line model [24]. β-lactoglobulin absorption undergoes two transcellular pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The main route is a degradative one, with a lysosomal processing of the protein. The second route allows the transcytosis of the intact protein for less than 10 % of the total transport [24]. These transcellular pathways could explain why its Papp was 4-fold lower than that of saturated avidin.…”
Section: Discussionmentioning
confidence: 99%